DAMPAK SOSIAL MEDIA TERHADAP SIKAP KEBERAGAMAAN REMAJA DAN SOLUSINYA MELALUI PENDIDIKAN AGAMA ISLAM - Eddy Saputra (Universitas Indraprasta PGRI, 2016)
Social media is impacting the lives and religious attitudes of teenagers. Only adolescents who have the background of religious education is not too worried. The teenager still have an awareness of religious values that once they get to irregularities committed only to the extent of lying and less responsible for his obligations. As for teenagers who do not have the educational background of religion much negative impact, because their actions had led to the crime.The development of information technology has penetrated freely in human life, especially among teenagers. In use many of them often ignore religious values and social. Crime rate stems from social media is increasing, as if emphasizing the use of social media has an impact on the implementation of the social and religious values, especially among teenagers. Keywords : Social media, diversity youth, religious education